Hierarchy Modification Effects in Catalytic Cracking of Palm Oil Using HZSM-5 Catalyst - Johan, Kelvin
Para-xylene is a petrochemical industry feedstock with a very high selling and demand level. However, in Indonesia, the high demand for para-xylene has not been matched by the high production of it domestically. In addition, para-xylene feedstock is generally still petroleum-based. One kind of green and clean way to produce para-xylene is through catalytic cracking of palm oil using HZSM-5 catalyst. However, without modification, HZSM-5 still has short lifetime and provides relatively low para-xylene selectivity. One alternative way to overcome the problems is by modifying the HZSM-5 used to hierarchical HZSM-5. The presence of the hierarchical structure is expected to prolong the catalyst lifetime and shift the xylene isomerization equilibrium towards para-xilene. The aims of this research were to determine the hierarchy modification effects on HZSM- 5 catalyst performances in cracking crude palm oil, especially from its selectivity towards para-xilene. The hierarchical HZSM-5 catalysts were synthesized by conducting desilication and dealumination against parent HZSM-5 already available in the TRKK Laboratory. In each of the run, the catalyst mass used was 2.5 g and the WHSV used was 2.5 h-1. The Si/Al HZSM-5 ratio used were 25, 50, and 80. The catalyst characterisation was done by conducting N2 isothermal adsorption test and TPD-NH3 test, while the product testing was done using GC-FID, GC-TCD, and GC-DHA. Coke mass analysis was done by thermogravimetry method. The conclusions drawn from this research were that hierarchy modification of HZSM-5 catalyst may prolong the catalyst lifetime, increase the aromatic selectivity stability, increase para-xilene selectivity (by around 1%), and slow down the coke formation rate compared to parent HZSM-5 catalyst. However, in its fresh condition, hierarchical HZSM-5 gave lower aromatic selectivity compared to parent catalyst. Moreover, hierarchical HZSM-5 also gave more gas product.